FRAMEWORK OF AN AMBIDEXTROUS PROCESS OF IDEA MANAGEMENT SUPPORTING THE DOWNSTREAM PRODUCT DEVELOPMENT PROCESS. (May 2020) - Herrmann, T.; Roth, D.; Binz, H.
Abstract: One challenge within idea management of the front end of the design process is the handling of radical ideas, meaning ideas with a high degree of novelty. Companies are approaching radical and incremental ideas frequently with the same methods, although many reasoned claims exists for treating ideas differently according to the degree of novelty. The paper aims to address the fact that ambidexterity does not play any specific role in the front end. Therefore, a framework of an extended idea process model based on the idea of ambidexterity is shown and initial test results are presented.